Anomalous Diffusion in a Membrane System - Kosztołowicz, T.; Lewandowska, K.D. (Ukrainian Journal of Physics, 2022)
We briefly discuss the physical basis of anomalous diffusion and equations with fractional derivatives, which describe this process. We also present the method of extracting subdiffusion parameters from experimental data.